The Effects of the Culturally Tailored Narratives on COVID-19 Vaccine Confidence Among Hispanics: A Randomized Online Experiment. Issue 3 (4th March 2023) - Hwang, Juwon; Cooley, Asya; Cooley, Skye; Hinck, Robert
Abstract : Guided by the health belief model (HBM), cultural sensitivity approach, and the theory of situated cognition, this study compares the effects of culturally tailored narratives and generic narratives on the COVID-19 vaccine confidence among Hispanics. It also examines an array of cognitive responses ( perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and perceived side effects) associated with the COVID-19 vaccine confidence, and the interaction of these cognitive responses with the two narrative types of messaging. The findings suggest that Hispanics exposed to culturally tailored narratives are more confident in the COVID-19 vaccine compared to Hispanics exposed to generic narratives. The study provides support for the HBM, as the perceived benefit was positively related to vaccine confidence, and the perceived barrier was negatively associated with vaccine confidence. Finally, vaccine confidence was the strongest among Hispanics who had high perceived susceptibility and were exposed to culturally tailored narratives.